Playing the ponies and other medical mysteries solved - Mushlin, Stuart B. (Rutgers University Press, 2017)
Master clinician Dr. Stuart Mushlin has cracked his share of medical mysteries. Recounting some of his most puzzling and illuminating cases, he reveals the challenges he's faced in a suspenseful page-turner, filled with real-life enigmas you'll have to read to believe. Playing the Ponies and Other Medical Mysteries Solved is a heartfelt reflection on forty years of patient care by one of America's "Best Doctors."